2015
DOI: 10.1021/acs.jpcc.5b10128
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Self-Assembly of Large Magnetic Molecules

Abstract: We have used two different unconventional preparation techniques, namely, pulse injection and rapid heating, to deposit large trinuclear transition-metal complexes onto a Au(111) surface under ultrahigh-vacuum conditions. Both techniques turn out to provide a clean preparation and leave the molecules intact upon deposition. While pulse injection leads to isolated molecules on the surface, rapid heating yields close-packed ordered monolayer islands. From a comparison of topographies and electronic structures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…However,t his perspectiveh ingesu pon the better understanding of their chemical and physical stability upon surface deposition, as till poorly studied subject. Surface deposition experiments have shown that chromium(III) carboxylate triangles [233] and the [Cu 3 (talen tBu2 )] complex [234] retain their structural integrity,a nd are encouraging in that regard. Clearly,h owever,f urthers tudies are required for as olid grasp of the issue, as achieved in the case of surface-deposited SMMs.…”
Section: Discussionmentioning
confidence: 94%
“…However,t his perspectiveh ingesu pon the better understanding of their chemical and physical stability upon surface deposition, as till poorly studied subject. Surface deposition experiments have shown that chromium(III) carboxylate triangles [233] and the [Cu 3 (talen tBu2 )] complex [234] retain their structural integrity,a nd are encouraging in that regard. Clearly,h owever,f urthers tudies are required for as olid grasp of the issue, as achieved in the case of surface-deposited SMMs.…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, a standard thermal sublimation was not feasible due to the fragility of these large complexes. We therefore utilized a pulse-injection technique for a clean in situ deposition of the molecules, which we have reported earlier [15]. After the preparation, the sample was immediately transferred into the cryogenic STM (operated at T = 5 K) and topography images were taken to identify single molecules and to acquire local tunneling spectra (dI/dV vs V, open feedback) as well as spectroscopic maps (dI/dV vs position, constant-current mode).…”
Section: Stm/sts Single-molecule Characterizationmentioning
confidence: 99%
“…In first approximation, dI/dV reflects the LDOS, where negative (positive) voltages correspond to (un)occupied states, and V = 0 defines the Fermi energy (E F ). Details of the sample preparation and STM/STS characterization have been published previously [15,34]. Figure 3 presents STM images of both molecules on Au(111).…”
Section: Stm/sts Single-molecule Characterizationmentioning
confidence: 99%
See 2 more Smart Citations